Lipoprotein Nanoplatform for Targeted Delivery of Diagnostic and Therapeutic Agents - Jerry D. Glickson; Sissel Lund-Katz; Rong Zhou; Hoon Choi; I-Wei Chen; Hui Li; Ian Corbin; Anatoliy V. Popov; Weiguo Cao; Liping Song; Chenze Qi; Diane Marotta; et al. (Molecular Imaging)
Low-density lipoprotein (LDL) provides a highly versatile natural nanoplatform for delivery of visible or near-infrared fluorescent optical and magnetic resonance imaging (MRI) contrast agents and photodynamic therapy and chemotherapeutic agents to normal and neoplastic cells that overexpress low-density lipoprotein receptors (LDLRs). Extension to other lipoproteins ranging in diameter from about 10 nm (high-density lipoprotein [HDL]) to over a micron (chylomicrons) is feasible. Loading of contrast or therapeutic agents onto or into these particles has been achieved by protein loading (covalent attachment to protein side chains), surface loading (intercalation into the phospholipid monolayer), and core loading (extraction and reconstitution of the triglyceride/cholesterol ester core). Core and surface loading of LDL have been used for delivery of optical imaging agents to tumor cells in vivo and in culture. Surface loading was used for delivery of gadolinium-bis-stearylamide contrast agents for in vivo MRI detection in tumor-bearing mice. Chlorin and phthalocyanine near-infrared photodynamic therapy agents (≤ 400/LDL) have been attached by core loading. Protein loading was used to reroute the LDL from its natural receptor (LDLR) to folate receptors and could be used to target other receptors. A semisynthetic nanoparticle has been constructed by coating magnetite iron oxide nanoparticles with carboxylated cholesterol and overlaying a monolayer of phospholipid to which apolipoprotein A1 or E was adsorbed for targeting HDL or adsorbing synthetic amphipathic helical peptides ltargeting LDL or folate receptors. These particles can be used for in situ loading of magnetite into cells for MRI-monitored cell tracking or gene expression.